2007
DOI: 10.1507/endocrj.k06-161
|View full text |Cite
|
Sign up to set email alerts
|

An Elderly Patient with Sarcoidosis Manifesting Panhypopituitarism with Central Diabetes Insipidus

Abstract: Abstract. We here report a 77-year-old Japanese male who suffered general fatigue with progressive thirst and polyuria. Central diabetes insipidus was diagnosed by depletion of vasopressin secretion in response to increases in serum osmolality. Secretory responses of anterior pituitary hormones including adrenocorticotropin, thyrotropin, gonadotropins and growth hormone were severely impaired. Diffuse swelling of the infundibulum as well as lack of T1-hyperintense signal in the posterior lobe was noted by pitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…There have been few case reports that diabetes insipidus could be cured in this situation, except for one spontaneous remission case (11). It has been considered that anterior pituitary function is difficult to restore, because hypopituitarism is not improved although the thickened pituitary stalk and enlarged pituitary gland return to their normal shapes after steroid treatment (3,12). However, a few case reports have shown that steroid therapy is able to partially improve anterior pituitary hormone secretion, which was confirmed by an endocrine provocation test (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been few case reports that diabetes insipidus could be cured in this situation, except for one spontaneous remission case (11). It has been considered that anterior pituitary function is difficult to restore, because hypopituitarism is not improved although the thickened pituitary stalk and enlarged pituitary gland return to their normal shapes after steroid treatment (3,12). However, a few case reports have shown that steroid therapy is able to partially improve anterior pituitary hormone secretion, which was confirmed by an endocrine provocation test (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes insipidus is one clinical manifestation of neurosarcoidosis in patients with involved pituitary lesions (2), and this presentation of the disease is generally not cured by steroid treatment (3). In contrast, whether glucocorticoid administration improves the endocrine dysfunction of the anterior pituitary gland in neurosarcoidosis is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The steroid therapy is a major treatment for CNS sarcoidosis (1,5,6 It is reported that CNS sarcoidosis progressively deteriorates and has a poor prognosis (7). In a literature of CDI due to sarcoidosis (10) …”
Section: Clinical Coursementioning
confidence: 99%
“…The incidence is 6 out of 100,000 persons in a year, and affects mainly objects in 20s to 40s (1). About 5% of patients with sarcoidosis have central nervous system (CNS) sarcoidosis (5,6) (3,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…76,79 This can lead to a panhypopituitarism. 80,81 In some cases, a pituitary lesion from sarcoidosis itself can be found. 82 In patients with panhypopituitarism, replacement with thyroid and glucocorticoid medications should be given.…”
Section: Endocrine Manifestationsmentioning
confidence: 99%